Proceedings of the Eleventh Annual International Conference on International Computing Education Research 2015
DOI: 10.1145/2787622.2787722
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Changes in Computer Science Students' Implicit Theories of Intelligence Across the Semester

Abstract: Our study was based on exploring CS1 students' implicit theories of intelligence. Referencing Dweck and Leggett's [5] framework for implicit theories of intelligence, we investigated (1) how students' implicit theories changed over the course of a semester, (2) how these changes differed as a function of course enrollment and students' self-regulation profiles, and (3) whether or not implicit theories predicted standardized course grades and performance on a computational thinking knowledge test. For all stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Even when learners complete these courses, they still score poorly on tests of basic coding knowledge [33]. Worse yet, recent work has found that introductory CS courses can convince learners' that their abilities are fixed and cannot be improved with practice [21,49], deterring them from not only learning to code, but learning any new skill.…”
Section: Introductionmentioning
confidence: 99%
“…Even when learners complete these courses, they still score poorly on tests of basic coding knowledge [33]. Worse yet, recent work has found that introductory CS courses can convince learners' that their abilities are fixed and cannot be improved with practice [21,49], deterring them from not only learning to code, but learning any new skill.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, we have studied how student models determined by education research in the form of student motivated engagement profiles [6,11,14,16] can be used to predict student behaviors in technology-mediated instruction and e-learning environments. Considering 7 CS1 courses with 249 students spanning 3 semesters, we investigated how students with different engagement profiles behaved in an online, wiki-based CSCL system while performing collaborative creative thinking exercises.…”
Section: Discussionmentioning
confidence: 99%
“…A learned helpless student who is motivated to engage but ineffective in their learning and strategies, eventually causing them to lose motivation and begin to disengage. Recent studies have found these five profiles among undergraduate CS, engineering, and other STEM students taking CS1 courses [6,11,16]. In these CS courses, students adopting the strategic and knowledge builder profiles have higher course achievement and learning [11,16].…”
Section: Background 21 Motivated Engagement Profilesmentioning
confidence: 97%
See 1 more Smart Citation
“…By contrast, Flanigan et al [7] analyzed (without intervention) changes in students of CS courses across the semester, nding a signi cant increase in xed mindset and a signi cant decrease in growth mindset.…”
Section: Background and Related Workmentioning
confidence: 99%